Effects of Supersuppressor Genes on Enzymes Controlling Lysine Biosynthesis in Saccharomyces - Fjellstedt, Tho̊rsten A. (1970)
Yeast supersuppressor genes capable of masking the effects of several lysine mutant genes (ly(1-1), ly(9-1), ly(2-1)) were studied with respect to their effects on the respective enzymes (saccharopine dehydrogenase, saccharopine reductase, and α-amino-adipic acid reductase). In all strains tested, the supersuppressors functioned by allowing enzyme synthesis not found in the unsuppressed mutant. Studies by optical methods of saccharopine dehydrogenase and saccharopine reductase extracted from suppressed ly(1-1) and ly(9-1) cells, respectively, revealed that the K(m) values for these enzymes were significantly greater than those found in wild type. Saccharopine dehydrogenase from suppressed ly(9-1) cells was found to have K(m) values similar to wild type. These findings are consistent with the inference that a supersuppressor may act by enabling nonsense codons to be read, producing altered enzyme protein. Recent findings that lysine degradation in mammals may involve saccharopine and that the human diseases, hyperlysinemia and saccharopinuria, may be due to metabolic blocks in this route of lysine degradation suggest the ly(1-1) and ly(9-1) yeast mutants as models for the human condition and its possible euphenic treatment.